Magnesium and anion requirements of rodB mutants of Bacillus subtilis. - Rogers, H J (1976)
rodB mutants of Bacillus subtilis have been found to require several hundred-fold more Mg2+ in a minimal growth medium than the wild type to achieve rapid growth. In the presence of all concentrations of Cl-, the organisms grow as deformed cocci, but with 10 mM Mg2+ and Br-, I-, or NO3- present they grow as rods. The morphology is then directly under the control of the concentration of both Mg2+ and anion. Originally, it was found that L-glutamic acid in the medium brought about the change from deformed spheres to rods. This amino acid will similarly function at a much lower concentration when the higher concentrations of Mg2+ and Cl- are also present. At a constant concentration of L-glutamate, the morphology can be controlled by varying the Mg2+ concentration. In the presence of Mg2+ and I-, the morphological change is temperature sensitive. At 30 C rods are formed and at 42 C deformed cocci are formed. The requirement of a rodB mutant for a high concentration of magnesium and the round morphology have been shown to be most probably due to a single mutation.